(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The present paper deals with Baldwin’s debut novel ‘Go Tell It On the Mountain’ with a view point of autobiographical elements and racial trauma pertaining to the dull insight of Christianity, racial and gender discrimination which he experienced in his own life. The novel is filled with Baldwin’s feelings and emotions inked with the very tongue spoken by the dim American. A deep study of the novel reveals that it is a complex story interwoven with the stories of John, the protagonist’s mother, fathers and aunts with its focus on the role of religion, race and gender in their lives at Harlem ghetto where a number of black people including the protagonist in novel and Baldwin in reality, migrated from the southern part of the US for a better future but in reality it has been proved an illusion because religious minority (the black people) are pushed to the margin by the majority community (the white people) who treated the black people as animals, second citizens and objects to be beaten, raped and killed in the broad light of the day.